Nanoparticle–cell–nanoparticle communication by stigmergy to enhance poly(I:C) induced apoptosis in cancer cells. Issue 53 (1st June 2020) - Ultimo, Amelia; de la Torre, Cristina; Giménez, Cristina; Aznar, Elena; Coll, Carmen; Marcos, M. Dolores; Murguía, José R.; Martínez-Máñez, Ramón; Sancenón, Félix
Abstract : Nanoparticle–cell–nanoparticle communication by stigmergy was demonstrated using two capped nanodevices. Abstract : Nanoparticle–cell–nanoparticle communication by stigmergy was demonstrated using two capped nanodevices. The first community of nanoparticles ( i.e. S(RA)IFN ) is loaded with 9- cis -retinoic acid and capped with interferon-γ, whereas the second community of nanoparticles ( i.e. S(sulf)PIC ) is loaded with sulforhodamine B and capped with poly(I:C). The uptake of S(RA)IFN by SK-BR-3 breast cancer cells enhanced the expression of TLR3 receptor facilitating the subsequent uptake of S(sulf)PIC and cell killing.